1994
DOI: 10.3758/bf03199951
|View full text |Cite
|
Sign up to set email alerts
|

Motivational control of goal-directed action

Abstract: The control of goal-directed, instrumental actions by primary motivational states, such as hunger and thirst, is mediated by two processes . The first is engaged by the Pavlovian association between contextual or discriminative stimuli and the outcome or reinforcer presented during instrumental training . Such stimuli exert a motivational influence on instrumental performance that depends upon the relevance of the associated outcome to the current motivational state of the agent . Moreover, the motivational ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
693
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(713 citation statements)
references
References 64 publications
17
693
3
Order By: Relevance
“…Thus, the model improves corticostriatal weights by simulating experience with the Extended TD model (Sutton and Barto, 1981;Sutton and Barto, 1998). Consistent with this simulation result, motor performance for human and animals can be improved by stimulating planning processes (Dickinson and Balleine, 1994;Decety, 1996).…”
Section: Planningsupporting
confidence: 56%
See 2 more Smart Citations
“…Thus, the model improves corticostriatal weights by simulating experience with the Extended TD model (Sutton and Barto, 1981;Sutton and Barto, 1998). Consistent with this simulation result, motor performance for human and animals can be improved by stimulating planning processes (Dickinson and Balleine, 1994;Decety, 1996).…”
Section: Planningsupporting
confidence: 56%
“…Animals learn act outcomes and select their acts based on the motivational value of these outcomes (reviews in Thistlethwaite, 1951;MacCorquodale and Meehl, 1954;Mackintosh 1974;Dennett 1978;Dickinson 1980;Dickinson 1994;Dickinson and Balleine 1994;Balleine and Dickinson 1998). Such goal-directed behavior is termed "planning" in reinforcement learning studies, or "cognition" in animal learning studies (Craik 1943;Sutton andBarto, 1981, 1998;Sutton and Pinette 1985;Dickinson 1994). Planning and sensorimotor learning were demonstrated for rats in T-maze experiments ( Fig.…”
Section: Planning and Sensorimotor Learning Animal Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…These three features are dissociable, but rely on partially overlapping neural mechanisms . Incentive salience in this context is distinct from incentive motivational properties or "incentive value" in instrumental settings as defined by Dickinson and colleagues (Dickinson and Balleine, 1994;Dickinson et al, 2000).…”
Section: Abilitymentioning
confidence: 92%
“…Such operant actions imply the ability to know that one is performing an action, and to represent its consequences (Dickinson & Balleine, 2000). Research on the epistemic content and conscious experience of action has identified two distinct processes underlying this ability.…”
Section: Introductionmentioning
confidence: 99%